A bibliometric analysis of ohmic heating on food processing in the last two decades - Purnama Ningsih S. Maspeke; Salengke Salengke; Junaedi Muhidong; Andi Dirpan (Heliyon)
Novel food processing technologies have been devised to cater to the specific requirements of consumer products and tackle the challenges associated with conventional food processing technologies. Ohmic heating is a contemporary thermal-process technology with advantages for time efficiency, improved sensory and functional quality, and enhanced energy efficiency. This bibliometric investigation aimed to analyze the level of scholarly research on ohmic heating within the field of food research over the past twenty years (2003–2023). The findings indicate an upward annual growth rate of 11.09 % in the subject of food-related ohmic heating research. A total of 769 publications have been published, involving 1841 authors. Brazil is recognized as the nation with the most research contributions while Sastry, S.K., is the most productive author, and Teixeira, J.A. is the most collaborative author. Review studies examining the impact of ohmic processes on the nutritional composition of fruits, vegetables, and grains have garnered the highest number of citations. Innovative Food Science and Emerging Technologies and the Journal of Food Engineering have emerged as the most influential journals in this field. Keywords such as “ohmic heating,” “electroconductive heating,” and ”joule heating” are commonly used in academic publications on the application of ohmic heating in the food industry. Recent trends in this field focus on aspects such as extraction procedures, pasteurization, physicochemical components, and energy usage. Ohmic heating has a bright future. Rapidly growing research shows strong interest, especially recently, because of attractive advantages such as energy efficiency and sustainability. International collaborations will expand its applications in the food industry. Challenges include high capital costs, maintenance, and unclear regulations. Future research should focus on cost-effective materials, thermal stability, food safety, and broader applications. With a clear path, the food industry can adopt ohmic heating technology as affordable and ecofriendly technology more efficiently.